62.10=(20+.5x)+.15(20+.5x)

Simple and best practice solution for 62.10=(20+.5x)+.15(20+.5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 62.10=(20+.5x)+.15(20+.5x) equation:


Simplifying
62.10 = (20 + 0.5x) + 0.15(20 + 0.5x)

Remove parenthesis around (20 + 0.5x)
62.10 = 20 + 0.5x + 0.15(20 + 0.5x)
62.10 = 20 + 0.5x + (20 * 0.15 + 0.5x * 0.15)
62.10 = 20 + 0.5x + (3 + 0.075x)

Reorder the terms:
62.10 = 20 + 3 + 0.5x + 0.075x

Combine like terms: 20 + 3 = 23
62.10 = 23 + 0.5x + 0.075x

Combine like terms: 0.5x + 0.075x = 0.575x
62.10 = 23 + 0.575x

Solving
62.10 = 23 + 0.575x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.575x' to each side of the equation.
62.10 + -0.575x = 23 + 0.575x + -0.575x

Combine like terms: 0.575x + -0.575x = 0.000
62.10 + -0.575x = 23 + 0.000
62.10 + -0.575x = 23

Add '-62.10' to each side of the equation.
62.10 + -62.10 + -0.575x = 23 + -62.10

Combine like terms: 62.10 + -62.10 = 0.00
0.00 + -0.575x = 23 + -62.10
-0.575x = 23 + -62.10

Combine like terms: 23 + -62.10 = -39.1
-0.575x = -39.1

Divide each side by '-0.575'.
x = 68

Simplifying
x = 68

See similar equations:

| 5/8-2/5 | | (10x)(5x)= | | T(30)=3.8(30)-2.5 | | 3xyz+2zxy-7zyx+2xy= | | -5a^2b^3-(-3)a^2b^2= | | x^4+4x^3+8x^2+8x-3=0 | | 4/20+12/20 | | -5a^2b^3-(-3a^2b^2)= | | 5r+15=6r-10 | | 2xy-3xyz= | | -6y+13=-18y-23 | | y+10=-(x-15) | | 5u+2v-2(4u-5v)= | | .75(.25x+8)-(25x+2)=0.375(4-x)-.25x | | X/19=5/95 | | -6y-12=-18y-23 | | 6x-12=x-22 | | y-2=3(x+1) | | 15/45=x/12 | | x^2-20x-98=0 | | 9b+4=2b+46 | | 25r^3-16r=0 | | 25r^3-16r=0 | | 11-8x=7x+17 | | 139-5x=3x-19 | | 2(x+6)=3(x-4)+5 | | q-7/4=3 | | v/11=5/3 | | -42-2x=6-6x | | 7-9x=7x+18 | | (7x^3+4x)(x^2+2)= | | 4(x-3)=23-x |

Equations solver categories